Pengaruh Fee Audit dan Masa Perikatan Audit Terhadap Kualitas Audit - Eldi Puji Resza; Poppy Sofia Koeswayo; Sony Devano (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to analyze the effect of audit fee and audit tenure on audit quality. The research method used is a quantitative research method with a descriptive and verification approach. The unit of analysis in this study was the Public Accounting Firm and the observation units were 39 fellowship partners. Hypothesis testing was carried out using multiple linear regression analysis method. The results of the hypothesis test show that partially audit fee have a positive and significant effect on audit quality, while audit tenure has no effect on audit quality. While simultaneously the audit fee and the audit tenure have a positive and significant effect on audit quality.